"Many lives, many masters" - "Weiss, Brian" (London, 1994)
Many Lives, Many Masters: The True Story of a Prominent Psychiatrist, His Young Patient and the Past-life Therapy That Changed Both Their Lives
Keywords: Prominent psychiatrist